The Shift of Addressing Terms of Mandailingnese Society in Panyabungan - Rica Umrina Lubis; Indah Tamara (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
This study deals with the shift of addressing term of Mandailingnese society in Panyabungan. It employs qualitative research design with a case study. This study aims to describe: (1) the types of shift occur in the use of addressing terms by Mandailingnese speaker in Panyabungan, (2) the pattern of the shift of addressing term and (3) Reasons of Mandailingnese shift the addressing term in Panyabungan. The subjects were 20 respondent from second generation of parents group. The instruments used in this study were questionnaire and interview. The data was analyzed by Miles and Hubermans’ data analysis. There are fourteen respondent (70%) shif completely the addressing term in core family, two respondent (10%) shift partly the addressing term and four respondent (20%) maintain the addressing term. The shift of ddressing terms cover three types; ten respondents (50%) do not participate actively in the life of minority language, three respondents (15%) are not fluent in Mandailing language and seven respondents (35%) those are influenced by their parents to shift the addressing term. There are five patterns of the shift of addressing terms and three reasons why Mandailingnese society shift the addressing term; status of Indonesian language, social success and family tradition. Keyword : shift, addressing term, mandailingnese society